Development of Academic Assessment Management Information System (Case Study: KB & TK Permata Iman) - Antono, Firnanda Ifitah Dewi; Wicaksono, Satrio Agung; Pinandito, Aryo (Journal of Information Technology and Computer Science, 2018)
Education becomes an important thing to advance a nation. Therefore, everyone must follow the education level. One of education level is early childhood education. KB & TK Permata Iman which was established in 2005 is a private educational institution and focus on early childhood education. In learning evaluation, KB & TK Permata Iman still use conventional method. The conventional method takes much time because teachers need to collect daily grade until the end of a semester for final grade calculation and prepare the results in grade book. The semester learning evaluation process can be shortened and simplified using a web-based academic assessment management information system. The system can store, directly perform calculations when teachers add students’ grade and make grade book from saved grade. From the testing result, the time efficiency increased to 94.94% when evaluating semester learning using the system and it can help the teacher to save time and do another task.